Hark, hark! Hear the story of a science educator - Ebenezer, Jazlin V. (Boca Raton, FL ; London : C & H/CRC Press, 2020)
Hark, Hark! Hear the Story of a Science Educator highlights some compelling ideas on science teaching and learning through the author's journey and includes evolution and revolution in the growth of scientific knowledge. The book discusses views of McComas et al. and Lederman et al. on the nature of science, as well as the learning theories of Piaget (1926), Vygotsky (1978), and Marton (1981). The three theories of learning frame methods in teaching science. The author is well known in the science education research community for her groundbreaking work in student conceptions and conceptual change, particularly as related to phenomenography. Key Features: Helps science educators explore new avenues related to various innovative curricula, teaching, and learning Presents abstract learning theories, such as social constructivism in personal stories and experiences Bridges the divide between the science education community and the general public on significant ideas of science teaching and learning Uncovers relational conceptual change inquiry learning Discusses current socioscientific community-based issues--other-centeredness--through scientific investigation and engineering design challenges
Treading the academic waters -- You are too lazy! -- Evolving educator -- The science banqueting table -- A multitude of 60-watts, amber light bulbs glowing on earth -- HyperCard to artificial intelligence for relational learning -- Engineering for learning science embedded in societal issues -- Pythagorean Theorem: An architecture for curriculum design.
OCLC-licensed vendor bibliographic record.
Keywords: Science teachers -- United States -- Biography; Science -- Study and teaching -- United States; MEDICAL / General; MEDICAL / Administration; SCIENCE / Chemistry / General